The effect of induction method in twin pregnancies: a secondary analysis for the twin birth study - Mei-Dan, Elad (BMC Pregnancy Childbirth, 2017)
BACKGROUND: This secondary analysis for the Twin Birth Study, an international, multicenter trial, aimed to compare the cesarean section rates and safety between methods of induction of labor in twin pregnancies. METHODS: Women with twin pregnancies where the first twin was in a cephalic presentation and who presented for labor induction, were non-randomly assigned to receive prostaglandin or amniotomy and/or oxytocin. Main outcome measures were the rates of unplanned cesarean section and neonatal and maternal mortality or serious morbidity. RESULTS: 153 (41.5%) were induced by prostaglandin (prostaglandin group) and 215 (58.5%) were induced by amniotomy and/or oxytocin alone (no prostaglandin group). Induction using prostaglandin was more common in countries with a low perinatal mortality rate <10/1000 (45.7 versus 32.5%, p = 0.02). Cesarean section rates were similar in the two groups: 62/153 (40.5%) in the prostaglandin group and 87/215 (40.5%) in the no prostaglandin group (odds ratio 1, 95% CI 0.65-1.5). Nulliparity, late maternal age, non-cephalic presentation of twin B and high country’s perinatal mortality rate were found to be independently associated with the induction to end with an unplanned cesarean section. There were no significant differences between groups with respect to maternal or neonatal adverse outcomes. CONCLUSIONS: The need for cervical ripening by prostaglandin had no effect on the incidence of cesarean delivery or an abnormal outcome. There is a significant risk of unplanned cesarean section independent of chosen induction method. TRIAL REGISTRATION: This trial was registered at the International Standard Randomized Controlled Trial Register (identifier ISRCTN74420086; December 9, 2003) and retrospectively registered at the www.clinicaltrials.gov (identifier NCT 00187369; September 12, 2005). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12884-016-1201-8) contains supplementary material, which is available to authorized users.